Design a power divider for a radar antenna receiver system / Mohamad Asri Shafie - Shafie, Mohamad Asri (2007)
Limitation in the current Radar system is incomplete measurement and incomplete sampling, due to the quality of the receiving signal. The Radar system is a very expensive set-up; therefore there is a crucial need for a backup system to enhance the system capabilities. The proposed backup system can be used for monitoring and surveillance purposes. Accurate data can be determined based on the quality of pickup or receiving signal, thus one of the important area is to maintain the quality of receiving signal by designing a power divider. Conventional power divider operates at a fundamental frequency and odd harmonics. This project focuses on the design of a microwave power divider with the capability of operating at multi frequencies. The design made use of the odd and even mode approaches to determine the power divider circuit parameters for suitable power division. The design starts with the conventional power divider which was simulated using AWR Microwave Office 2004. Further modifications have been performed on the basic power divider. The circuit performances are investigated using Scattering parameters related to a multi-port network. These include the return loss, isolation, forward and transmission coefficients. The simulation results are then analyzed and compared.